KOPERASI SECARA ISLAM DALAM KERANGKA PERUNDANGAN MALAYSIA - Buang, Ahmad Hidayat (Jurnal Syariah, 2019)
With the rapid and vigorous development of Islamic banking and finance in Malaysia, more people including of those who are non-Muslims are already familiar with the principles of Islamic mu 'amalat applicable in banking, finance, investment and insurance. For this reason, very much attention has been given to above subjects. Little has been written on the subject of cooperative societies from the Islamic law point of view. This is however not unusual, as the conventional aspect of this subject was also less observed by other writers. Attention from Islamic point of view on the subject of cooperative societies is opportunely needed since many of its principles are said to be compatible with Islamic Shari 'ah. This perception is therefore encouraging from the viewpoint of economics activities of the Muslims. In the view of current aggressive development in Islamic banking and finance, this article attempts to show the financial activities of cooperative societies as practiced in Malaysia is another viable alternatives to conventional banking, finance and investment. Some recommendations to amend certain provisions of the laws are made in order to ensure the system complies with the principles of the Syariah.